PENINGKATAN KUALITAS PEMBELAJARAN FISIOLOGI HEWAN DENGAN PENGEMBANGAN BAHAN AJAR BERKARAKTER BERBASIS HASIL PENELITIAN - Beno Wahono; umie Lestari; Abdul Gofur (Bioedukasi Jurnal Pendidikan Biologi, 2013)
This study aims to improve the quality of learning by developing character-based teaching materials research animal physiology courses. This research method is the development of module manufacturing as a source of learning based on the research that has been done, including a description, picture research and implementation process that include sites expected character, whether written or unwritten is adapted from Dick and Carey learning system to make some adjustments. The results obtained are based on the calculation and conversion of valuation module by module expert instructional materialsby 71, 66%. Based on the results of the conversion, the preparation of the module other wise well qualified and do not need to be revised. The results of the assessment calculation and conversion modules by physiologists by 85%. Based on the results of  the conversion, the module qualification other wise excellent preparation and do not need to be revised. Conclusion are obtained the results by the developing of characterized teaching materials based on the results of experiment is feasible and can be used to support lectures to enhance the quality of teaching Animal Physiology courses in college.Kata kunci: Kualitas pembelajaran fisiologi hewan, bahan ajar berkarakter